JUSTIFICATION OF THE PARAMETERS OF SHIELDING STRUCTURES TO COUNTER TEMPEST THREATS - Kozlovsky, Valerii; Balanyuk, Yurii; Kozlovska, Diana; Vyshnevska, Nataliia (Science-based technologies, 2026)
In the era of digital transformation and escalation of cyber espionage threats, physical protection of information acquires the status of a critical condition for ensuring national security. The article is devoted to the study and justification of engineering parameters of shielding structures aimed at effective counteraction to TEMPEST threats. The relevance of the study is enhanced by the growing intensity and broadband of radiation generated by modern high-performance equipment (servers, communication systems), which requires the use of specialized protective solutions. Recommendations are substantiated for optimizing key physical parameters of shielding structures necessary to ensure a guaranteed level of attenuation of side electromagnetic radiation in accordance with international standards. A comparative characteristic of TEMPEST protection levels according to SDIP-27 and NSTISSAM standards is provided. It is proven that the effectiveness of the screen is achieved due to two main mechanisms - reflection (dominant at high frequencies) and absorption of electromagnetic waves by the material. The calculated formulas for the reflection and absorption coefficients demonstrate their critical dependence on the ratio of wave resistances and screen thickness. The features of flat and perforated screens are considered. Successful counteraction to TEMPEST threats lies in the synergy between the material and the design. It has been established that the most promising for broadband protection are materials that combine high conductivity and absorption capacity. It has been proven that the implementation of calculation methods at the design stage allows predicting the protective properties of materials, taking into account the spatial distribution of metal inclusions, which significantly minimizes the volume of costly full-scale tests and simplifies the procedure for planning electromagnetic safety work. The results of the study are a fundamental basis for developing engineering solutions that meet the highest requirements of international electromagnetic safety.